Charged domain wall modulation of resistive switching with large ON/OFF ratios in high density BiFeO3 nano-islands. (1st April 2020) - Han, M.J.; Tang, Y.L.; Wang, Y.J.; Zhu, Y.L.; Ma, J.Y.; Geng, W.R.; Feng, Y.P.; Zou, M.J.; Zhang, N.B.; Ma, X.L.
Abstract: Ferroelectrics exhibit polarization tunable resistance switching behaviors, which are promising for next-generation non-volatile memory devices. For technological applications, thinner nanoscale arrays are expected, which feature with higher density and larger ON/OFF (RON/OFF ) ratios in the metal/ferroelectrics/semiconductor heterojunction. Here, we acquire high density BiFeO3 (BFO) nano-islands around 10 nm in thickness displaying a high RON/OFF ratio of 10 3, comparable to the tunnel junctions. Moreover, both the macroscopic and microscopic resistive switching behaviors of the present BFO films reveal an unexpected filamentary-type resistive switching which is modified by the charged domain walls in nano-islands dominated by the center-type domains. Particularly, the charged domain walls spontaneously formed within the BFO nano-islands are proposed as the conductive paths based on the redistribution of carriers under the applied voltages. Potential applications for memories with large RON/OFF ratios of such kind of configurable charged domain walls are demonstrated. Graphical abstract: Image, graphical abstract